The Urals and Ukraine in the System of Interregional Contradictions of the 1920s — 1930s (Part 4) - M. V. Mikheev (Историко-географический журнал)
The study completes a series of articles devoted to the problem of interregional economic contradictions between the Urals and Ukraine in the USSR during the interwar period. The author examines the general economic trends that accompanied the coexistence of two industrial centers in the system of the state economy of the USSR during the Soviet industrialization in 1928–1940. The analysis of the dynamics of industrial production in the Urals and Ukraine in the context of all-union statistical indicators is carried out. The changes in interregional relations between the two regions during the specified period are analyzed based on the materials of transport statistics. It is shown that after the Soviet government chose an extensive path of industrial development, which was expressed in the scaling of industrial production in Ukraine, and the reorganization of the Ural industry by combining its iron ore resources with coal deposits in Western Siberia, the share of the two regions in the allUnion economy did not changed a lot. However, structurally, the Ural industry underwent radical changes, abandoning the charcoal metallurgy and combining with the productive forces of Western Siberia into a single territorial industrial complex. By the end of the 1930s, this complex had already demonstrated its economic self-sufficiency at the level of the extractive industry, but its manufacturing industry still continued to gravitate towards the European regions of the USSR. The establishment of the sectoral economic management apparatus by the central government in the early 1930s made it possible to overcome regionalist tendencies in the USSR. The latter ones, however, were replaced by the factor of interagency controversies in the economy, to combat which it was necessary to resort to the manifestations of regionalism again. Nevertheless, industrialization radically changed the geography of Soviet industry. The contradictions between the Urals and Ukraine have lost their acuteness and have dissolved among other interterregional and interagency conflicts. The article is accompanied by illustrative and cartographic materials.